ASSESSMENT OF THE FLOW RATE OF THE ZARAFSHAN RIVER ACCORDING TO CLIMATIC FACTORS - F, Hikmatov; S.A., Haydarov; Z.F, Hakimova; N.B., Erlapasov (International Journal of Psychosocial Rehabilitation, 2020)
This article gives a brief natural geographical description of the Zarafshan River Basin and evaluates its hydrometeorological researches. The connections between river flow and meteorological quantities, that are atmospheric precipitation and air temperature, were statistically analyzed. The regression equations representing these connections were taken and on the basis of them, the nomogram for assessing the flow of the river was drawn up. Using this nomogram, the amount of Zarafshan river flow was determined for different climatic scenarios.